2023
DOI: 10.3390/ijms241612637
|View full text |Cite
|
Sign up to set email alerts
|

Hybrids of Sterically Hindered Phenols and Diaryl Ureas: Synthesis, Switch from Antioxidant Activity to ROS Generation and Induction of Apoptosis

Elmira Gibadullina,
Margarita Neganova,
Yulia Aleksandrova
et al.

Abstract: The utility of sterically hindered phenols (SHPs) in drug design is based on their chameleonic ability to switch from an antioxidant that can protect healthy tissues to highly cytotoxic species that can target tumor cells. This work explores the biological activity of a family of 45 new hybrid molecules that combine SHPs equipped with an activating phosphonate moiety at the benzylic position with additional urea/thiourea fragments. The target compounds were synthesized by reaction of iso(thio)cyanates with C-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…I. Alabugin's research group in electrochemistry challenges the classical understanding of antioxidants and their properties [31]. By employing cyclic voltammetry with a semi-differential method, they unveiled new avenues in the quest for compounds that exhibit both antioxidant and anti-tumor properties.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…I. Alabugin's research group in electrochemistry challenges the classical understanding of antioxidants and their properties [31]. By employing cyclic voltammetry with a semi-differential method, they unveiled new avenues in the quest for compounds that exhibit both antioxidant and anti-tumor properties.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%
“…This collection of articles presents extensive research and discoveries that leverage various morphologies of electrochemical compositions, emphasizing their multifunctional properties, such as advanced redox properties [24][25][26][27][28][29][30][31]. The published articles range from the drug design and synthesis of hybrids of sterically hindered phenols and diaryl ureas [31] to sophisticated studies on the enhancement of arc erosion resistance in AgCuO electrical contact materials [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we found phenol derivatives that exhibit high cytotoxicity towards HuTu 80 and M-HeLa tumor cells due to the induction of apoptosis via mitochondrial pathway. An interesting feature of these compounds was a switch from redox protection to increased ROS production under the oxidative stress conditions typical for cancer cells [ 14 , 15 ]. Figure 1 A provides selected examples of phenol- and coumarin-containing biologically active substances, including anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%